2014
DOI: 10.1016/j.envexpbot.2013.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Future climate alleviates stress impact on grassland productivity through altered antioxidant capacity

Abstract: Predicting future ecosystem functioning requires a mechanistic understanding of how plants cope with different stressors under future climate conditions with elevated CO2 concentrations and warmer temperatures. Nonetheless, studies of stress responses under combined elevated CO2 and warming remain scarce. We assembled grassland communities in sunlit, climate-controlled greenhouses and subjected these to three stressors (drought, zinc toxicity, nitrogen limitation) and their combinations. Half of the communitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 61 publications
3
26
1
3
Order By: Relevance
“…The influence of high [CO 2 ] on other enzymes such as ADP-Glucose pyrophosphorylase, sucrose phosphate synthase, rubisco activase and PEPCase, in regulating carbon assimilation has also been studied. Increased activities of these enzymes resulted in higher levels of nonstructural carbohydrates including glucose, sucrose, fructose and starch (Makino and Mae, 1999;Davey et al, 2006;Fukayama et al, 2009;Ribeiro et al, 2012;AbdElgawad et al, 2014). The availability of additional photosynthates facilitates plants to grow faster under high [CO 2 ].…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…The influence of high [CO 2 ] on other enzymes such as ADP-Glucose pyrophosphorylase, sucrose phosphate synthase, rubisco activase and PEPCase, in regulating carbon assimilation has also been studied. Increased activities of these enzymes resulted in higher levels of nonstructural carbohydrates including glucose, sucrose, fructose and starch (Makino and Mae, 1999;Davey et al, 2006;Fukayama et al, 2009;Ribeiro et al, 2012;AbdElgawad et al, 2014). The availability of additional photosynthates facilitates plants to grow faster under high [CO 2 ].…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…oxidative pressure (Farfan-Vignolo and Asard, 2012;Naudts et al, 2014;Zinta et al, 2014 Phosphorous being a major constituent of nucleic acid (about 40-60% P in the cell), P deficiency affects RNA synthesis and protein synthesis, and thus inhibits metabolism including photosynthesis. Optimum photosynthesis requires 2.0-2.5 mM P is required in the chloroplast.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…The consistent patterns of Chl(a+b), Car and the Chl(a+b)/Car ratio were likely due to the lower rate of loss of Car than of Chl(a+b), which reflects an adaptive strategy because carotenoid plays an important role in photoprotection and antioxidation (Ebrahimiyan et al, 2013; Zhang et al, 2013). The information about increased antioxidant capacity under different stresses has been reported largely (Naudts et al, 2014; Xu et al, 2014, 2015). Decrease in antenna pigments such as Chl b suggested that plants experienced a process of antenna size readjustment.…”
Section: Discussionmentioning
confidence: 99%
“…The accumulation of APX and other defencerelated proteins in spring wheat grains under elevated CO 2 was also reported by Qiu et al (2008) and Högy et al (2009b). In plants, SOD and APX are two of the main ROS-scavenging enzymes, and constitute a highly efficient system for removing (Cheeseman 2006;Qiu et al 2008;Naudts et al 2014). This increased oxidative stress under elevated CO 2 might be due to increased canopy temperatures (Kimball et al 1999;Högy et al 2009b).…”
mentioning
confidence: 88%